1991
DOI: 10.1007/bf01964413
|View full text |Cite
|
Sign up to set email alerts
|

Pharmacokinetics of meropenem compared to imipenem-cilastatin in young, healthy males

Abstract: Imipenem combined with cilastatin and meropenem was given as intravenous infusions of 1 g to eight young, healthy males on two separate occasions. Blood and urine samples were collected for up to 12 h. The terminal half-lives in plasma were 0.98 h and 1.11 h for meropenem and imipenem, respectively. The volume of distribution was smaller for meropenem than for imipenem (12.5 l and 14.4 l, respectively). The plasma clearance for meropenem was 188 (SD 31) ml/min and for imipenem 183 (SD 25) ml/min. Renal clearan… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

4
40
1
5

Year Published

1994
1994
2020
2020

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 87 publications
(57 citation statements)
references
References 8 publications
4
40
1
5
Order By: Relevance
“…The pharmacokinetic properties of meropenem and imipenem administered as imipenem/cilastatin are comparable, following single and multiple dose administration (Nilsson-Ehle et al, 1991;Drusano, Yuen & Standiford, 1992) and, therefore, the same dosing regimen (1 g every 8 h) was employed for both antibiotics.…”
Section: Introductionmentioning
confidence: 99%
“…The pharmacokinetic properties of meropenem and imipenem administered as imipenem/cilastatin are comparable, following single and multiple dose administration (Nilsson-Ehle et al, 1991;Drusano, Yuen & Standiford, 1992) and, therefore, the same dosing regimen (1 g every 8 h) was employed for both antibiotics.…”
Section: Introductionmentioning
confidence: 99%
“…Meropenem, a carbapenem structurally related to imipenem, is stable to the majority of ␤-lactamases (23) and is active in vitro against a broad range of gram-negative and gram-positive aerobic and anaerobic bacteria, with several-fold-greater activity than that of imipenem against H. influenzae and N. meningitidis (4). Meropenem is also stable to human renal dehydropeptidase-I and, unlike imipenem, does not need to be combined with a dehydropeptidase inhibitor such as cilastatin (22).…”
mentioning
confidence: 99%
“…Usually, these antibiotics produce a PAE only against gram-positive strains and have a short or no PAE on gram-negative rods (22). On the contrary, different authors have demonstrated that carbapenems induce a consistent PAE both in vitro and in vivo against both grampositive and gram-negative strains, including Pseudomonas aeruginosa (1,3,6,7,15,18).…”
mentioning
confidence: 96%
“…Usually, these antibiotics produce a PAE only against gram-positive strains and have a short or no PAE on gram-negative rods (22). On the contrary, different authors have demonstrated that carbapenems induce a consistent PAE both in vitro and in vivo against both grampositive and gram-negative strains, including Pseudomonas aeruginosa (1,3,6,7,15,18).Meropenem is a new carbapenem which differs from imipenem in having a dimethylcarbamoylpyrrolidinethio side chain at C-2 which assures it a broad spectrum of activity against aerobes and anaerobes (9, 17). This carbapenem derivative has a pharmacokinetic profile very similar to that of imipenem and a consistent PAE even greater than that of imipenem (3,7,15,18).…”
mentioning
confidence: 99%
See 1 more Smart Citation